The concept of happiness and thought in Spanish Renaissance: the case of "Nueva filosofía de la naturaleza humana" (1587) - Arroyo Serrano, Santiago (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
In this article we analyse the importance of the concept of happiness in the Spanish Renaissance and especially in Nueva filosofía de la naturaleza humana (1587), considered one of the most important philosophical treatises of the Spanish Renaissance, as it links directly moods and happiness with health. In this work we recover the tradition that maintains how through the exercise of philosophy it is possible to achieve happiness, a relevant topic in Spanish humanism, which at the same time brings to the present some of the classical traditions.